Leaf colour chart based nitrogen management in wheat under zero till condition of West Bengal - Mondal, Triptesh; Mitra, Biplab (Indian Farming, 2022)
The climatic potential yield of irrigated wheat is about 5-7 t/ha in West Bengal but the actual yield obtained was much less i.e. 2.77 t/ha in 2017-18 resulting in a yield gap of 45- 60%. Improper nutrient management is one of the major factors for such yield gap. In West Bengal, most of the wheat crop is preceded by long-duration transplanted rice varieties such as Jalprabha (IET-11870), Saraswathi (IET-11271), Swarna (MTU-7029) and delayed harvest of paddy, delays the sowing of wheat towards the end of November to middle of December which is one of the major constraints of wheat cultivation in rice fallows. Hardly 10-15 days remain available between harvest of rice and timely sowing of wheat which puts tremendous pressure on land preparation and sowing of succeeding crop in time. Growing labour shortage in hightime also delays wheat sowing which affects the productivity of wheat adversely. As a result, zero tillage (ZT) technology has been increasingly adopted in this region to reduce cultivation cost and increase input use efficiency in wheat cultivation. Site Specific Nutrient Management-Nutrient Expert (SSNM-NE) is a recently developed precision nutrient management technology guided by the DSS (Decision Support System) software for improving crop yield, environmental quality and overall agricultural sustainability specifically in South-Asian Indo-Gangetic Plains Region (IGPR). Nutrient expert enables crop advisors to develop SSNM recommendations using existing site information. As fertilizer, nitrogen (N) has generally been managed following two or three split applications of preset rates of the total amount of N recommendation, and improvement in N use efficiency could not be achieved beyond a limit. Wheat leaf colour chart (LCC) is a diagnostic tool for monitoring the relative greenness of a leaf as an indicator of plant N status. N-scheduling through the use of LCC to achieve the best results regarding improved grain yield and economic returns over fixed time N application. A predetermined dose of N is applied using wheat LCC when a critical value or critical colour shade is obtained. It was observed that wheat yield and profit between 2016-17 to 2018-19 has an increasing trend.